Safety analysis of 250-kW Philippine research reactor-1 thermal-hydraulics under steady-state operations using MARS-KS code - Jecong, Julius Federico M.; Astronomo, Alvie A.; Hila, Frederick C.; Guillermo, Neil Raymund D.; Sweng Woong Woo (Philippine Journal of Science)
"The Philippine Nuclear Research Institute (PNRI) of the Department of Science and Technology (DOST) is implementing a project to use the Philippine Research Reactor 1- (PRR-1) TRIGA nuclear fuel in a subcritical reactor (SCR) for training, education, and research in nuclear science and technology. However, although an SCR is a valuable training and research facility, it offers limited industrial applications. To potentially reap more benefits, DOST-PNRI is also investigating the feasibility of converting the zero-power SCR to a low power critical reactor in the future. In this work, the thermal-hydraulic behavior of a hypothetical 250-kW low power configuration of the PRR-1 TRIGA reactor is investigated using the MARS-KS code"-title page.